Effect of Different Mediators on Bio-Energy Generation and Palm Oil Mill Effluent Treatment in an Air-Cathode Microbial Fuel Cell-Adsorption System - Ivy Tan, Ai Wei; J.R., Selvanathan; M.O., Abdullah; Noraziah, Abdul Wahab; Devagi, Kanakaraju (Trans Tech Publications Ltd., 2025)
Palm oil mill effluent (POME) discharged without treatment into watercourses can pollute the water source. Microbial fuel cell (MFC) has gained high attention as a green technology of converting organic wastewater into bio-energy. As an approach to overcome the limitations of the existing POME treatment methods, air-cathode MFC-Adsorption system is introduced as an innovative technology to treat POME and generate bio-electricity simultaneously. However, the use of conventional MFC with proton exchange membrane in large scale applications is restricted by the high cost and low power generation. Addition of mediator in MFC is essential in order to increase the electron transfer efficiency, hence enhancing the system performance. This study therefore aims to investigate the effect of different type of mediators i.e. congo red (CR), crystal violet (CV) and methylene blue (MB) on the performance of an affordable air-cathode MFC-Adsorption system made from earthen pot with POME as the substrate. The addition of different mediators altered the pH of the MFC-Adsorption system, in which more alkaline system showed better performance. The voltage generated in the system with CR, CV and MB mediator was 120.58 mV, 168.63 mV and 189.25 mV whereas the current generated was 2.41 mA, 3.37 mA and 3.79 mA, respectively. The power density of 290.79 mW/m³, 568.72 mW/m³ and 716.31 mW/m³ was produced in the MFC-Adsorption system with CR, CV and MB mediator, respectively. The highest POME treatment efficiency was achieved in MFC-Adsorption system with MB mediator, which resulted in biochemical oxygen demand, chemical oxygen demand, total suspended solids, turbidity and ammoniacal nitrogen removal of 75.3%, 84.8%, 91.5%, 86.1% and 23.31%, respectively. Overall, the air-cathode MFC-Adsorption system with addition of MB mediator was feasible for POME treatment and simultaneous bio-energy generation.